Decentralizatin and its impact on primary education outcomes - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
ABSTRACT Development outcomes nowadays not only measured by the successful of economic growth but more comprehensively by the achievement of human development. Obviously education has been place a one substantialfactor not only as a basic human right but also in international development. Meanwhile after more than 8 years of decentralization in Indonesia, many concerns arise regarding the decentralization impacts. One of the considerable questions is on how far the fiscal decentralization has enhanced education development achievement. Therefore, a set of fiscal decentralization variables used in this paper to analyze their roles on primary education ou!comes. Enrollment Rate used as dependent variable to represent the primary education outcomes. Regional characteristics were also utilized to improve the robus.t,n. ess of the result. Using panel data set of 434 sub provincial regions (districts and cities) in Indonesia, the estimation result show that fiscal decentralization instrument played a significant role on primary education outcomes. Furthermore, DAK seems to have a greater impact on primary education outcomes than DAU. Additionally the estimation result also shows that there is still a significant disparity among sub provincial region in primary education achievement. The results suggest that fiscal decentralization instrument rearrangement substantially needed next to the education development equalization in all sub provincial region. This way, decentralization will foster more favorable outcomes in education development outcomes hopefully. Keywords: decentralization,primary education,panel data. INTRODUCTION Economic growth used to be the most common measurement to portray the development outcomes. It measured how far have many factors in development utilized and contributed to the aggregate of national output. This measurement certainly has many significant contributions to the achievement of development. Certain level of economic 1 Paper